2019
DOI: 10.1016/j.porgcoat.2019.105248
|View full text |Cite
|
Sign up to set email alerts
|

Curing epoxy with ethylenediaminetetraacetic acid (EDTA) surface-functionalized Co Fe3-O4 magnetic nanoparticles

Abstract: In this work, the bulk and surface composition of Fe3O4 supermagnetic nanoparticles were modified for efficient epoxy curing. The bare, ethylenediaminetetraacetic acid (EDTA) capped, and cobalt (Co)-doped EDTA capped Fe3O4 nanoparticles were synthesized electrochemically.The crystalline nature and phase information of the nanoparticles, surface capping, morphology and magnetization of nanoparticles were studied by X-Ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), field emission scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…As shown in Figure 1 , surface functionalization of Co-doped MNPs with different molecules posed different effects on the cure state of epoxy. For instance, the use of ethylenediaminetetraacetic acid (EDTA) as surface modifier for Co-doped MNPs makes the cure Good [ 29 ]. On the other hand, Poor cure state is obtained in the case of epoxy containing polyvinyl chloride (PVC) functionalized Co-doped MNPs [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1 , surface functionalization of Co-doped MNPs with different molecules posed different effects on the cure state of epoxy. For instance, the use of ethylenediaminetetraacetic acid (EDTA) as surface modifier for Co-doped MNPs makes the cure Good [ 29 ]. On the other hand, Poor cure state is obtained in the case of epoxy containing polyvinyl chloride (PVC) functionalized Co-doped MNPs [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the conversion–time curves, increasing the heating rates from 2 to 10 °C∙min −1 accelerates the epoxide ring-opening curing reaction. By enhancing the molecules’ motion and raising the number of collisions in the epoxy/amine systems due to the higher kinetic energy per molecule at higher heating rates, the curing reaction is completed in a shorter time for all samples [ 39 ]. As demonstrated in Figure 7 , the epoxy nanocomposite consisting of Mg-Al-CO 3 -HA showed a higher curing rate at all heating rates and took less time for the reaction with respect to the two other samples, which is due to the incomplete curing of the EP/Mg-Al-CO 3 -HA.…”
Section: Resultsmentioning
confidence: 99%
“…The cure study of epoxy containing 0D spherical cobalt doped Fe 3 O 4 nanoparticles revealed that the amount of heat of cure of nanocomposite was significantly higher than that for the neat epoxy system due to the catalytic effect of nanoparticles [10]. In another study, surface modification of cobalt doped Fe 3 O 4 nanoparticles with ethylenediaminetetraacetic acid enhanced the curability of epoxy nanocomposite because of the reaction between the carboxylic acid anchored to the surface of particles and the epoxide rings [11]. Nonisothermal differential scanning calorimetry (DSC) results indicated that epoxy nanocomposite containing Ni-Al-NO 3 2D layered double hydroxide platelet-like nanoparticles increased the cross-link density of network compared to the unfilled epoxy due to the reaction of nitrate anion with epoxide ring [12].…”
Section: Introductionmentioning
confidence: 99%